Influence of extracapsular nodal spread extent on prognosis of oral squamous cell carcinoma. (30th October 2015) - Wreesmann, Volkert B.; Katabi, Nora; Palmer, Frank L.; Montero, Pablo H.; Migliacci, Jocelyn C.; Gönen, Mithat; Carlson, Diane; Ganly, Ian; Shah, Jatin P.; Ghossein, Ronald; Patel, Snehal G.
ABSTRACT: Background: An objective definition of clinically relevant extracapsular nodal spread (ECS) in head and neck squamous cell carcinoma (SCC) is unavailable. Methods: Pathologic review of 245 pathologically positive oral cavity SCC neck dissection specimens was performed. The presence/absence of ECS, its extent (in millimeters), and multiple nodal and primary tumor risk factors were related to disease‐specific survival (DSS) at a follow‐up of 73 months. Results: ECS was detected in 109 patients (44%). DSS was significantly better for patients without ECS than patients with ECS. Time‐dependent receiver operator curve (ROC) analysis identified a prognostic cutoff for ECS extent at 1.7 mm. In multivariate analyses, DSS was significantly lower for patients with major ECS compared with patients with minor ECS, but not significantly different between patients with minor ECS and patients without ECS. Conclusion: ECS is clinically relevant in oral cavity SCC when it has extended more than 1.7 mm beyond the nodal capsule. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1192–E1199, 2016